2023
DOI: 10.1093/migration/mnad015
|View full text |Cite
|
Sign up to set email alerts
|

Newly arrived migrants meet street-level bureaucrats in Jordan, Sweden, and Turkey: Client perceptions of satisfaction–dissatisfaction and response strategies

Isabell Schierenbeck,
Andrea Spehar,
Tareq Naseef

Abstract: The article examines how newly arrived Syrian refugees experience and navigate their encounters with street-level bureaucrats (SLBs) in three urban settings: Adana, Turkey; Gothenburg, Sweden; and Irbid, Jordan. The encounters took place in the context of local government institutions responsible for assisting refugees upon their arrival in the host society. The broader question examined is how refugees respond when experiencing dissatisfaction with their encounters with SLBs in the receiving country. In our a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Whilst participants did not disclose how they responded to their challenging interactions with street-level bureaucrats, other studies have suggested that migrants are likely to respond in one of five main ways: Exiting the situation, such as by trying to subvert formal systems or switch service provider; Voicing their concerns through complaints or speaking up; Remaining loyal to the street-level bureaucrat by continuing with the process without speaking up; Neglecting the situation by becoming indifferent; or Gaming the system by trying to exploit or manipulate the rules in their favour (Schierenbeck et al 2023). Whilst formal complaint procedures to raise concerns with civil servants in Spain exist, they are unlikely to be used in the context of immigration procedures given the precarious status of the applicants, the inherent power imbalance and the extent to which street-level bureaucrats acting in this field are 'protected from external examination' and 'empowered to interpret and apply legal texts and regulations without, in most cases, having to fear administrative appeals' (Alpes and Spire 2013).…”
Section: Interpersonal Communication With Public Officialsmentioning
confidence: 99%
“…Whilst participants did not disclose how they responded to their challenging interactions with street-level bureaucrats, other studies have suggested that migrants are likely to respond in one of five main ways: Exiting the situation, such as by trying to subvert formal systems or switch service provider; Voicing their concerns through complaints or speaking up; Remaining loyal to the street-level bureaucrat by continuing with the process without speaking up; Neglecting the situation by becoming indifferent; or Gaming the system by trying to exploit or manipulate the rules in their favour (Schierenbeck et al 2023). Whilst formal complaint procedures to raise concerns with civil servants in Spain exist, they are unlikely to be used in the context of immigration procedures given the precarious status of the applicants, the inherent power imbalance and the extent to which street-level bureaucrats acting in this field are 'protected from external examination' and 'empowered to interpret and apply legal texts and regulations without, in most cases, having to fear administrative appeals' (Alpes and Spire 2013).…”
Section: Interpersonal Communication With Public Officialsmentioning
confidence: 99%